A Positive Cooling Feedback for the Neoproterozoic Snowball Earth Initiation Due To Weakening of Ocean Ventilation - Peng Liu; Yonggang Liu; Sifan Gu; Paul Hoffman; Sanzhong Li (Geophysical Research Letters, 2023)
Abstract Ocean ventilation is an important regulator for atmospheric CO2 level (pCO2) by affecting the relative proportion of carbon stored in the atmosphere and deep ocean. Expansion of sea ice during glacial periods slows down ocean ventilation and its effect is expected to be the largest during the Neoproterozoic pre‐snowball stage. Here, our Community Earth System Model version 1.2.2 simulations demonstrate that averaged deep ocean ventilation age almost triples when the climate cools from a warm state with negligible sea ice to one in which the global sea‐ice coverage reaches ∼50% when pCO2 is lowered to 280 ppmv. Further cooling by reducing pCO2 from 280 to 70 ppmv increases the ventilation age from 1900 to 2300 years. This latter small increase in deep‐ocean ventilation age can reduce pCO2 by 48 ppmv, assuming Neoproterozoic organic production was comparable to present level. Therefore, the weakened ocean ventilation constitutes a significant positive feedback to the Late Neoproterozoic climate cooling.